2020
DOI: 10.1039/d0cc04299d
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nanotubes self-assembled from leucine-rich alpha helical surfactant-like peptides

Abstract: The designed arginine-rich surfactant-like peptide R3L12 (arginine3-leucine12) is shown to form a remarkable diversity of self-assembled nanostructures in aqueous solution, depending on pH, including nanotubes, mesh-like tubular networks in three-dimensions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…2c. These branched nanotubes are very similar to those previously reported by us for 0.04 wt% R 3 L 12 at pH 1, 51 which we proposed are built from a-helical antiparallel peptide dimers arranged perpendicular to the nanotube wall. The branching is believed to result from the increased energetic penalty of charged residues at nanotube ends at low pH.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…2c. These branched nanotubes are very similar to those previously reported by us for 0.04 wt% R 3 L 12 at pH 1, 51 which we proposed are built from a-helical antiparallel peptide dimers arranged perpendicular to the nanotube wall. The branching is believed to result from the increased energetic penalty of charged residues at nanotube ends at low pH.…”
Section: Resultssupporting
confidence: 90%
“…In our recent Communication, we showed that it forms nanotubes (at pH 2-4) or nanotubular networks (at pH 1) in acidic aqueous solutions. 51 Here we show that nanotube network structures are formed at pH 7 and pH 9, and we present new data showing the a-helical conformation of the peptide in the nanotubes, for the first time from synchrotron SAXS with an extended q range covering the spacing associated with a-helical structures, as well as CD and FTIR spectroscopy. This provides a unique combination of structural and spectroscopic probes of the a-helical structure.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations